D meson elliptic flow in noncentral Pb-Pb collisions at √sNN=2.76 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Fasel, Markus; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; et al. (Physical review letters, 2013)
Azimuthally anisotropic distributions of D0, D+, and D*+ mesons were studied in the central rapidity region (|y|<0.8) in Pb-Pb collisions at a center-of-mass energy √sNN=2.76 TeV per nucleon-nucleon collision, with the ALICE detector at the LHC. The second Fourier coefficient v2 (commonly denoted elliptic flow) was measured in the centrality class 30%-50% as a function of the D meson transverse momentum pT, in the range 2-16 GeV/c. The measured v2 of D mesons is comparable in magnitude to that of light-flavor hadrons. It is positive in the range 2<pT<6 GeV/c with 5.7σ significance, based on the combination of statistical and systematic uncertainties.
Im Titel steht "sNN" unter dem Wurzelsymbol
Im Titel ist "NN" in sNN tiefgestellt
The ALICE collaboration: B. Abelev, V. Angelov, O. Busch, M. Fasel, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, M.J. Kweon, D. Lohner, X.-G. Lu, A. Maire, J. Mercado-Pérez, H. Oeschler, K. Oyama, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, J. Ulrich, M.A. Völkl, Y. Wang, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann und weitere 948
Gesehen am 29.04.2021